2020
DOI: 10.1016/j.renene.2019.07.096
|View full text |Cite
|
Sign up to set email alerts
|

Thermal cracking behavior, products distribution and char/steam gasification kinetics of seawater Spirulina by TG-FTIR and Py-GC/MS

Abstract: In this study, fast pyrolysis of seawater Spirulina, is carried out to evaluate the potential of deriving valuable chemicals and fuel molecules from this seawater algae variety. The devolatilization behavior and gaseous product evolution of seawater Spirulina were carried out by TG-FTIR. Py-GC-MS was employed to investigate the composition and distribution of volatile products formed from the seawater Spirulina through high-temperature fast pyrolysis process. Finally, the seawater Spirulina char gasification r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Comparing the FT‐IR spectrum of this initial degradation peak of GL and G50‐S50 ( Figure A, spectra a and b) reveals large O─H stretching (3500–4000 cm −1[ 40 ] ) and H 2 O bending (1550–1680 cm −1[ 41 ] ) absorption bands, which can be assigned to the evolution of water and possibly some other ─OH─containing functionalities, e.g., alcohols, phenolics. This water would originate from the dehydration reactions that occur at this temperature during the pyrolysis of GL.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the FT‐IR spectrum of this initial degradation peak of GL and G50‐S50 ( Figure A, spectra a and b) reveals large O─H stretching (3500–4000 cm −1[ 40 ] ) and H 2 O bending (1550–1680 cm −1[ 41 ] ) absorption bands, which can be assigned to the evolution of water and possibly some other ─OH─containing functionalities, e.g., alcohols, phenolics. This water would originate from the dehydration reactions that occur at this temperature during the pyrolysis of GL.…”
Section: Resultsmentioning
confidence: 99%
“…The above results indicate that some part of oxygen species in sawdust transfer into semicoke because of the transformation of phenol hydroxyl into polycyclic compounds linked with oxygenated functional group. 7,24 Liu et al 26 also reported that the main oxygen species in the semicoke was phenol hydroxyl that could form stable structures with aromatic ring through a strong π bond due to the conjugation of lone pair of electrons existing on the oxygen of phenol hydroxyl.…”
Section: Xps Analysismentioning
confidence: 99%
“…It was reported that carbon originated from biomass may adhere to the surface of coal, and inhibited the evolution of volatile matter, and then promoteed the mesophase formation 22 ; Hydrogen in biomass may act as the fluidity enhancers to promote the formation of coal plasticity, and favored for developing an optical anisotropic mosaic 14,18,23 ; Higher content of oxygen in biomass not only inhibits the formation of mesophase, but also prevents the development of the anisotropic structure. 19,[24][25][26] The microporosity of the semicoke derived from biomass/coals co-coking was also increased by the catalytic activity of the alkali and alkaline earth metal (AAEMs). 27,28 The incorporation of biomass into the blending coal may also significantly affect the physiochemical structure of the semicoke derived from co-carbonization of biomass/coal blends such as the functional groups, carbon structure, surface morphologies, and optical texture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermogravimetric analysis combined with infrared spectroscopy (TG-IR) and pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) is the most common way to estimate pyrolysis behavior and byproducts of biomass, polymers, and even waste (Li et al 2017a;Chen et al 2019;Li et al 2020). The TG-IR method allows facile evaluation of pyrolysis by determining the decomposition characteristics and products as well as the measurement of multiple gas products in a complex matrix simultaneously and in real-time (Ferreira et al 2019).…”
Section: Introductionmentioning
confidence: 99%